KARAKTERISASI KEKUATAN GESER DAN STRUKTUR MIKRO HASIL SPOT WELDING PELAT BAJA KARBON RENDAH: CHARACTERIZATION OF SHEAR STRENGTH AND MICRO STRUCTURE OF SPOT WELDED RESULTS OF LOW CARBON STEEL PLATES - Paryanto Dwi Setyawan; I Made Suniartha; Sugiman; Sinarep (Energy, Materials and Product Design, 2024)
Spot welding is a joining method that utilizes thermal energy generated by the resistance of electric current. Research was conducted to determine the effect of plate thickness, current and welding time on the characteristics of spot welding results. Spot welding was performed on low carbon steel plates of 0.8 mm, 1.5 mm and 1.8 mm thickness with current (50, 60, 70, 80 amperes) and welding time (10, 15, 20 seconds). Characterization of the spot welds was done by shear test (ASTM D1002-10) and observation of macro and micro structure (ASTM E3-11) and failure surface of the specimens. From the research conducted, it is known that the average shear strength increases with decreasing plate thickness, increasing welding current and decreasing welding time. The highest average shear strength of 502,772 N/mm2 was obtained with a plate thickness of 0.8 mm, a welding current of 70 A, and a welding time of 10 seconds. For thin plates, most of the shear test specimens failed in the area of the heat affected zone, while for thick plates, most of the shear test specimens failed in the area of the nugget spot weld.